Dosariyah : an Arabian neolithic coastal community in the Central Gulf - Drechsler, Philipp, (British Foundation for the Study of Arabia monographs ;, 2018)
This monograph describes the work carried out by the joint German-Saudi Dosariyah Archaeological Research Project (DARP) between 2010 and 2014 at Dosariyah, located in the Eastern Province of Saudi Arabia.